Testing for Pro-Poorness of Growth through the Tax System: The Mexican Case - Huesca, Luis; Llamas, Linda (Journal of Reviews on Global Economics, 2016)
This research provides a detailed examination of the redistributive effect achieved by the tax system including total taxes and cash transfers targeting the contributors and households in the period 2002-2008-2014 for the Mexican regions and the country. We measure the impact on income growth through the tax system according to each fiscal rules for the corresponding years using pre and post fiscal conditions. We answer the next question: considering the economic growth on per capita incomes in the Mexican states, will the impact of the Mexican tax system improve income distribution? That is, by all means pro-poor? Our methodology allows to detect if taxes and benefits can really induce an improvement of income growth on the regions captured by its wellbeing and economic growth conditions. We outlined relevant theoretical issues on public fiscal policies concerning this work and lastly, we proceed with an empirical application to develop some recommendations for the Mexican fiscal policy system.